THE IMPLEMENTATION OF ENGLISH IMMERSION PROGRAM FOR FACING GLOBALIZATION ERA - Santi Andriyani (Universitas Islam Nahdlatul Ulama Jepara, 2016)
This study is aimed at describing English immersion program on Indonesian students as the second speakers. The writer uses Descriptive study to explain the concepts and significances of English immersion program. It describes how the immersion program is conducted and how the type, technique and strategy are implemented. The result of this study shows that the English immersion program gives many advantages. The students tend to have many kinds of vocabularies and English achievements. Immersion classes are expected to be the answer to the key issues to improve competitiveness in globalization era. That??s why immersion class will equip the students with strategic ways to have good competence in English skills. The study also shows that immersion class is different from the traditional language course. It is due to the fact that traditional course uses target language as simply the subject material. Meanwhile, immersion class uses the target language as a teaching tool where students actively get involved in surrounding or ??immersing? class.